Tinjauan Pelaksanaan Audit Koding Berkas Pengklaiman Pasien Peserta BPJS Kesehatan di Rumah Sakit Umum Imelda Pekerja Indonesia Tahun 2021 - Sitorus, Mei Sryendang; Simanjuntak, Esraida; Gusla, Yeyi; Olviya , Cicha (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2023)
The coding audit is a review to ensure that the results of the diagnosis and treatment coding produced by the clinical coder are accurate, consistent and timely when compared to the information contained in the patient's medical record. The purpose of this study was to determine the implementation of the coding audit and to find out the efforts made to minimize the non-compliance of claims to the BPJS Health at Imelda Pekerja Indonesia Hospital in 2021. The type of research used was qualitative research with the number of informants as many as three coders who took Total Sampling. The research instrument used was an interview guide with qualitative descriptive data analysis techniques. Based on the results of the study, it was found that the level of knowledge of coding audit officers about coding audits is quite good but coding audits are still carried out post-claims and there are no instruments in implementing coding audits while the person in charge of coding audits at Imelda General Hospital is the Medical Committee, Verifier Internal, Quality Control and Cost Control Teamand Koder. Suggestions from researchers should Imelda Pekerja Indonesia Hospital socialize the coding audit SPO, then the coding audit is carried out pre-claim and in its implementation a coding audit instrument is made.